FELICITY CONDITIONS AS A FRAMEWORK FOR UNDERSTANDING INCOMPETENT DISCOURSE: BRIDGING THE CONCEPTS OF RUWAIBIDAH AND THE DUNNING–KRUGER EFFECT - Yanti, Aprili; Ezir, Ely (Universitas Islam Sumatera Utara, 2025)
This study investigates how felicity conditions—a fundamental concept in speech act theory—serve as an analytical framework for understanding incompetent discourse, particularly at the intersection of Ruwaibidah (a prophetic term referring to unqualified individuals who speak on public affairs) and the Dunning–Kruger Effect (a psychological bias in which people with limited ability overestimate their competence). By integrating insights from Islamic ethics, pragmatics, and cognitive psychology, the research examines how violations of key felicity conditions—sincerity, authority, appropriateness, and truthfulness—manifest as epistemic and moral failures in public communication. Drawing on case studies from Indonesian political discourse, the study reveals how such violations distort meaning, erode public trust, and contribute to the normalization of incompetent speech. Ultimately, the paper proposes that felicity conditions offer a comprehensive normative lens for evaluating the ethical legitimacy and epistemic integrity of speech acts, fostering a deeper interdisciplinary understanding of responsible discourse and communicative competence within social and political contexts.